The Contrast in BMI, the Age Group, and the Risk Factors for Car-diovascular Disease in Jordanian Men - Jafar Al Arjan (My University, 2010)
This study is based on a sample of (742) middle-age men (16.60±42.22) with a range of (20-83) year, cardiovascular risk factors (T-c, HDL-c, LDL-c, TG, T-c/HDL, Homocysteine and hypertension) were measured for them, so that members of the sample were divided according to the variability of the BMI to three categories:(< 0.25), (>-0.25 < 29.99), (≥ 30.0) (k.g/m2). The results indicated that the statistically significant difference in the BMI is a sign of high rates of risk factors for cardiovascular disease; these rates have raised in proportions in obese individuals compared to non-obese individuals, and that these risk factors are attributed to the increase in the age group, noted that there are indicators of these dangerous factors for the age group less than (40) Years. In light of that, it is recommended to include a programs to alleviate the proportion of fats in the body as an important element of prevention and treatment for individuals who suffer from the presence of risk factors for cardiovascular disease, in addition to the need for a national strategy aimed at countering its spreading especially for young people, in particular, with regard to the pattern of daily life.

تهدف الدراسة إلى التعرف على أثر التباين في مؤشر كتلة الجسم والمرحلة العمرية على عوامل الخطورة للإصابة بالأمراض القلبية الوعائية لدى الرجال الأردنيين ونسب تواجدها، حيث تكونت عينة الدراسة من (742) رجلاً بمتوسط عمر (42.22± 16.60) وبمدى من (20- 83) سنة. قيست لهم عوامل الخطورة للإصابة بالأمراض القلبية الوعائية (الكولسترول الكلي، الكولسترول مرتفع الكثافة، الكولسترول منخفض الكثافة، دهنيات الدم الثلاثية، نسبة الكولسترول الكلي/الكولسترول مرتفع الكثافة، الهيموسيستائين وضغط الدم، بحيث تم تقسيم أفراد العينة تبعاً لمتغير مؤشر كتلة الجسم إلى ثلاث فئات هي: (< 25.0)، (< 25.0- > 29.99)، (≤ 30.0) (كغم/م2). أشارت النتائج إلى وجود تأثير إحصائي دال للتباين في مؤشر كتلة الجسم على ارتفاع نسب عوامل الخطورة للإصابة بالأمراض القلبية الوعائية، حيث ارتفعت لدى الأفراد البدناء قياساً إلى الأفراد غير البدناء، وهذه العوامل الخطرة تزداد نسبها مع الزيادة في الفئة العمرية، إلا أن الملاحظ وجود مؤشرات خطرة لارتفاع تلك العوامل للفئة العمرية أقل من (40) سنة. وفي ضوء ذلك، يوصى بضرورة إدراج برامج تخفيف نسبة الشحوم في الجسم، كجزء هام في البرنامج العلاجي والوقائي لدى الأفراد الذين يعانون من تواجد عوامل الخطورة للإصابة بالأمراض القلبية الوعائية، إضافة إلى ضرورة إيجاد استراتيجية وطنية تهدف إلى مجابهة انتشارها، وبخاصة لدى فئة الشباب وصغار السن فيما يتعلق بالنمط الحياتي اليومي.
التباين في مؤشر كتلة الجسم والمرحلة العمرية وتأثيرهما على عوامل الخطورة للإصابة بالأمراض القلبية الوعائية لدى الرجال الأردنيين